2009
DOI: 10.1590/s1413-86702009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in brazilian pediatric patients: using a decision tree to identify high mortality groups

Abstract: Nosocomial infections (NI) are frequent events with potentially lethal outcomes. We identified predictive factors for mortality related to NI and developed an algorithm for predicting that risk in order to improve hospital epidemiology and healthcare quality programs. We made a prospective cohort NI surveillance of all acute-care patients according to the National Nosocomial Infections Surveillance System guidelines since 1992, applying the Centers for Disease Control and Prevention 1988 definitions adapted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…A review about the safety of maternal pneumococcal vaccination found no differences in stillbirth [ 9 , 16 ], spontaneous abortions [ 16 ], congenital birth defects [ 16 ], or prematurity rates [ 17 ] in women who were vaccinated compared to those who were not [ 18 ]. These studies only found the expected effects including local tenderness or pain [ 10 , 13 , 14 , 17 ], swelling [ 10 , 13 , 14 ], or fever [ 10 , 13 , 14 , 17 ]. Hence, all current studies support the safety of maternal pneumococcal vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…A review about the safety of maternal pneumococcal vaccination found no differences in stillbirth [ 9 , 16 ], spontaneous abortions [ 16 ], congenital birth defects [ 16 ], or prematurity rates [ 17 ] in women who were vaccinated compared to those who were not [ 18 ]. These studies only found the expected effects including local tenderness or pain [ 10 , 13 , 14 , 17 ], swelling [ 10 , 13 , 14 ], or fever [ 10 , 13 , 14 , 17 ]. Hence, all current studies support the safety of maternal pneumococcal vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, maternal immunization can be applied to other (live-attenuated) vaccines and infectious diseases as well. However, it has been reported that maternal immunization with a pneumococcal (polysaccharide) vaccine does not protect infants against clinical disease (165). …”
Section: Induction Of Maternal Antibodies Through Maternal Immunizatimentioning
confidence: 99%
“…Mukai et al 69 performed a spatial analysis of hospitalizations for pneumonia in the Vale do Paraiba region of Brazil that determined spatial autocorrelations and identified cities in which interventions are necessary regarding the number of hospitalizations for pneumonia in infants under one year of age. Lopes et al 70 studied the immunization of 139 mothers with pneumococcal capsular polysaccharide vaccine during pregnancy randomly allocated to receive/not receive 23-valent polysaccharide vaccines during or after pregnancy. Their offspring were monitored monthly over the first 6 months of life, and the results showed that providing the mother with a polysaccharide vaccination during pregnancy did not decrease pneumococcal colonization.…”
Section: Methodsmentioning
confidence: 99%